KINERJA KARYAWAN DENGAN KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL INTERVENING - Muhammad Reza Soekamto Putra; Hero Priono; Gideon Setyo Budi (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2018)
The purpose of this study was to analyzetest the quality of the system and the quality of accounting information system of information on the performance of employees at PT BPR HARTA SWADIRI Pasuruan, quality of the systems and quality of accounting information system of information on employee performance to user satisfaction intervening variable accounting information system at PT BPR HARTA SWADIRI. This research is a quantitative research methods approach questionnaire (questionnaire), data collection techniques done by questionnaire. Data analysis techniques in this study using Partial Least Square (PLS).Findings from this study indicate that the quality of accounting information system of employee performance showed their support to contribute but for the quality of accounting information system of employee performance is still not too make a contribution, hence the satisfaction of users of accounting information systems with the quality of accounting information systems and the quality of accounting information systems able to strengthen employees in improving the performance of the employee.